Government Spending Contributions on per Capita Income and its Effect toward the Human Development Index (Comparative Study between Western Indonesia and Central & East Indonesia) - Sofilda, Eleonora; ., Muhammad Zilal Hamzah (Journal of Social and Development Sciences, 2015)
In many countries, include Indonesia, a centralized government has a sizeable negative impact on inequality of development. During the New Regime Order era with a centralized system, Indonesia’s development is concentrated in the western part of Indonesia which had led to inequality in terms of per capita income and human development. To solve these problems, one of the economic reforms undertaken by the Indonesia government is changes the system from a centralized to a decentralized system. Through the fiscal decentralization under Law No. 22/99 and 25/99, they hope to improve people’s welfare and reduce inequality. This research is aim to assess the effect of government spending and investment on the growth of per capita income and see the effect of the growth of per capita income towards Human Development Index (HDI). The method used is multiple regression with panel data and the study from year 2007-2012 by dividing the two groups of regions ie: western Indonesia and central&eastern Indonesia. Based on the research results, for the western Indonesia, goods and services expenditure has a significant effect on the per capita income growth and per capita income growth significantly affect the human development index (HDI). For the central and eastern Indonesia, domestic and foreign direct investment (DDI and FDI), goods and services expenditure, and capital expenditures have a significant effect toward per capita income growth and per capita income growth effect significantly toward the HDI.